Strategi Komunikasi Organisasi Komunitas Rumah Internet Dalam Membangun Minat Belajar Anak di Era Digital - Tiara Nitami (Universitas Muhammadiyah Sumatera Utara, 2023)
This research examines how the process of Organizational Communication Strategy of the Rumah Internet Community in Building Children's Learning Interest in the Digital Era. Children's learning interests in cities and villages have significant differences. The difference occurs because of the education gap between urban and rural areas. In addition, the existence of the internet and the unstoppable flow of information also causes children's lack of interest in learning. This can lead to high dropout rates in children, especially in Desa Kurandak. This research was conducted to find out how the Communication Strategy of the Internet House Organization in Building Children's Learning Interest in the digital era. The type of research used in this research is a qualitative approach. This research type uses a descriptive qualitative type. The data collection techniques used are interview, observation, and documentation techniques. The resource persons in this research amounted to 2 (two) people who are the Founders of the Rumah Internet and the Board of Supervisors of the Rumah Internet Community. The results of this study show that the communication strategy of the Rumah Internet community organization to children is delivered and carried out well, can be well received, and is right on target so as to produce changes. In building children's interest in learning in the digital era, Rumah Internet utilizes the presence of the digital era to attract children's attention, to create interest, and to build children's feelings of pleasure in learning.Â The digital era is the most important thing in building children's interest in learning in Desa Kurandak because children in the village feel happy and interested when learning using digital technology